2014
DOI: 10.3399/bjgp14x677527
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of referral to a domestic violence advocate in UK primary care settings: a service-user collaborative study

Abstract: INTRODUCTIONIdentification and Referral to Improve Safety (IRIS) is a training and support programme for general practice that aims to improve the response to women experiencing domestic violence and abuse (DVA). The programme trains clinicians in identification, initial response or validation, referral to specialist DVA advocacy, and continuing support.In a cluster randomised trial the IRIS intervention had a substantial effect on identification of women experiencing DVA and on referral to DVA advocacy.1 A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 12 publications
5
50
0
Order By: Relevance
“…A separate thematic analysis of this data set exploring women's experience of the role of advocates in GP referral is reported elsewhere (Malpass et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A separate thematic analysis of this data set exploring women's experience of the role of advocates in GP referral is reported elsewhere (Malpass et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The findings of that study are reported elsewhere (Malpass et al . ). This paper explores our intention to reduce as much as possible the ‘symbolic violence’ inherent in the research encounter (Bourdieu , ).…”
Section: Introductionmentioning
confidence: 97%
“…Women often lack confidence that their primary care doctor or general practitioner (GP) can offer help, but those who do disclose abuse value the empathetic communication, validation of their situation and referral for additional help that may follow . However, disclosure without appropriate referral may leave women vulnerable and a major trial showed that GPs, to identify abuse, need both dedicated training and a clear referral pathway to specialist advocacy . Little is known about the part played by health professionals in women's overall help‐seeking strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This, combined with discussions about safety planning and options for ending violence can be a valuable and empowering means of problem-solving and building self-efficacy in this context [2123, 25, 26]. Some studies have found that having a focal person at the health centre who is specially trained on violence and dedicated to the issue can be an important element in responding to violence [27]; others identified support groups as a potentially positive intervention option [28]. In general, research has confirmed the value of interventions to address partner violence in antenatal care settings and suggests that even a single counselling session can result in improved safety behaviours and reduced levels of intimate partner violence [21, 22].…”
Section: Introductionmentioning
confidence: 99%